(3GdOQI GdeVjI aj bQGAGJ GdCFeI GdKdGKI GdeQVjIs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , (B833 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; bGd TjNfG TjN GdESdGe eMeO Hf eMeO Hf GdLRQj (B: (3bd GdMeO ddg GdPj hMOg YdG heLOg hGSCd Yhfg hJhSdG (B- (3hUd Ydi NjQ GdCfGe eMeO hSde hBd hGdUMGH hef JdGs
(3BNQgG (B:s
(3aCOQcfj GddWa GdNaj hQOfj YfjRI MJi LGAfj ef JcadG (B- (3HMedj hEjUGdj dWjHI BefG ajG QH HdZfj eQGOj hSgdG (B- (3hef HLeY GdTed hGZaQ PfhHfG hUd Ydi NjQ GdCfGe hef JdGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 45s
(3eYLe GdeDdajf (B3 / 687s
(3cTa GdXfhf (B1 / 743s
(3TPQGJ GdPgH (B7 / 204s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs